Case 3750: Dasypeltis atra Sternfeld, 1912 (Reptilia, Serpentes): proposed precedence over Dasypeltis lineolata Peters, 1878 - Bates, Michael F (Bulletin of Zoological Nomenclature)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the specific name Dasypeltis atra Sternfeld, 1912 which is in widespread use for a widely distributed species of snake (family Colubridae) from central and eastern Africa by giving it precedence over its seldom-used senior synonym Dasypeltis lineolata Peters, 1878. Dasypeltis lineolata was used as a valid name in 1884 and 1894, and then again only in 2016.
Keywords: Nomenclature; taxonomy; Reptilia; Squamata; COLUBRIDAE; Dasypeltis atra; Dasypeltis lineolata; Africa; montane egg-eating snake